Latin American financial markets developments in financial innovations - Arbeláez, Harvey; Click, Reid W. (International finance review ;, 2005)
This book is a collection of 21 original papers on Latin American finance by prominent researchers in and out of the region. This is an attempt to bring them together under the same umbrella so that the commonality and peculiarity of Latin finance can be more easily discerned across different applications as well as compared across countries. While topics are diverse (encompassing corporate finance, banking, equity and bond markets, dollarization, and pension funds), the papers range from country-specific to comparative and international in perspectives.